Kinetics of Bacteriophage λ Deoxyribonucleic Acid Infection of Escherichia coli - Barnhart, Benjamin J. (1965)
Barnhart, Benjamin J. (Los Alamos Scientific Laboratory, University of California, Los Alamos, N.M.). Kinetics of bacteriophage λ deoxyribonucleic acid infection of Escherichia coli. J. Bacteriol. 90:1617–1623. 1965.—The kinetics of Escherichia coli K-12 infection by phage λ deoxyribonucleic acid (DNA) were determined. An initial lag of 55 to 80 sec was found to be the time required for infecting DNA to become deoxyribonuclease-insensitive at 33 C. When cell-DNA interactions were stopped by washing away unbound DNA, the already bound DNA continued to infect the cell at rates described by linear kinetics with no apparent lag. Whereas the lag period was relatively insensitive to DNA and cell concentrations, both the lag and the subsequent linear portions of the rate curves were temperature-sensitive. Cell and DNA dose-response curves prescribed hyperbolic functions. Similarities between λ DNA infection of E. coli and bacterial transformation systems are discussed.